(untitled) (AmeriQuests, 2021)
This article analyses the engagement in cultural and creative practices of people of South Asian heritage in the borough of Tower Hamlets in London and in Loughborough, East Midlands. Both locations are home to a number of community groups engaged in creative and cultural activities and, by focusing on selected case studies, we argue that the arts play a key role in maintaining and claiming South Asian heritage/s in Britain. Comparing these two sites and the activities of key groups located there paves the way for an understanding of the role of the arts in the negotiation of diasporic identities in the UK: these activities and their broader collective engagement offer insights into participants’ experiences of inclusion and exclusion, intercultural relations and solidarity.